Cooperative halogen bonding and polarized π-stacking in the formation of coloured charge-transfer co-crystals. (10th April 2018) - Nwachukwu, Chideraa I.; Kehoe, Zachary R.; Bowling, Nathan P.; Speetzen, Erin D.; Bosch, Eric
Abstract : Matched electron rich halogen bond acceptors and donor have been synthesized and the halogen bonded charge transfer cocrystals characterized. Abstract : Red co-crystals are formed between the matched complementary electron rich halogen bond acceptors, isomeric 4-( N, N -dimethylamino)phenylethynylpyridines and the electron poor halogen bond donor, 1-(3, 5-dinitrophenylethynyl)-2, 3, 5, 6-tetrafluoro-4-iodobenzene. The red 1 : 1 cocrystals exhibit strong halogen bonding and strong π-stacking. The N⋯I distances range from 2.80 to 2.85 Å and the C–I⋯N angles are between 169.9 and 175.8°. In all four structures the donor and acceptor molecules are alternately π-stacked with the centroid to centroid distances between the dinitrophenyl moiety and the dimethylaminophenyl moiety ranging from 3.61 to 3.73 Å. The calculated π–π stacking binding energy is −22.24 kcal mol −1 for the complex between 4-[4-( N, N -dimethylamino)phenylethynyl]pyridine and 1-(3, 5-dinitrophenylethynyl)-2, 3, 5, 6-tetrafluoro-4-iodobenzene while the calculated halogen bond binding energy between the same couple is −7.97 kcal mol −1 .